Hyperemesis gravidarum and placental dysfunction disorders. Issue 1 (December 2016) - Koudijs, Heleen; Savitri, Ary; Browne, Joyce; Amelia, Dwirani; Baharuddin, Mohammad; Grobbee, Diederick; Uiterwaal, Cuno
Abstract Background Evidence about the consequence of hyperemesis gravidarum (HG) on pregnancy outcomes is still inconclusive. In this study, we evaluated if occurrence of hyperemesis gravidarum is associated with placental dysfunction disorders and neonatal outcomes. Methods A prospective cohort study was conducted in a maternal and child health primary care referral center, Budi Kemuliaan Hospital and its branch, in Jakarta, Indonesia. 2252 pregnant women visiting the hospital for regular antenatal care visits from July 2012 until October 2014 were included at their first clinic visit. For women without, with mild and with severe hyperemesis, placental dysfunction disorders (gestational hypertension, preeclampsia (PE), stillbirth, miscarriage), neonatal outcomes (birth weight, small for gestational age (SGA), low birth weight (LBW), Apgar score at 5 min, gestational age at delivery) and placental outcomes (placental weight and placental-weight-to-birth-weight ratio (PW/BW ratio)) were studied. Results Compared to newborns of women without hyperemesis, newborns of women with severe hyperemesis had a 172 g lower birth weight in adjusted analysis (95%CI -333.26; -10.18;p  = 0.04). There were no statistically significant effects on placental dysfunction disorders or other neonatal outcome measures. Conclusions The results of our study suggest that hyperemesis gravidarum does not seem to induce placental dysfunction disorders, but does, if severe lead to lower birth weight.